Efektivitas manajemen pemantauan risiko: Studi kasus dalam industri perbankan di BTPN - Mubarok, Ahmad Zaki (Maliki Interdisciplinary Journal, 2023)
The banking industry faces increasingly complex risks, making risk management crucial to minimize risks and maintain business continuity. One important aspect of risk management is continuous risk monitoring. This study aims to evaluate the effectiveness of risk monitoring management in the banking industry, with a focus on Bank BTPN as a case study. The research method used is a qualitative approach with a case study approach. Data was collected through interviews with Bank BTPN employees involved in risk management, as well as through document and policy analysis related to risk management. The results show that Bank BTPN has adopted best practices in banking risk management and complies with applicable regulatory requirements. Bank BTPN also involves employees in risk training and awareness to ensure they understand the risks associated with their tasks and responsibilities. However, the effectiveness of Bank BTPN’s risk monitoring is influenced by factors such as management commitment, expertise and resources, policies and procedures, information systems and reporting, as well as compliance and supervision. Therefore, Bank BTPN needs to continue to improve risk management and strengthen the factors that affect the effectiveness of risk monitoring. In conclusion, this study provides insights into the effectiveness of risk monitoring management in the banking industry, with a focus on Bank BTPN as a case study.